STUDI LITERATUR: PENGARUH PENERAPAN MODEL CTL TERHADAP KEMAMPUAN KONEKSI MATEMATIS SISWA DAN SELF EFFICACY SISWA - Zubaidah Amir MZ; Fitria Rizka Mulyani (Prodi. Pendidikan Matematika, FKIP, Universitas Riau, 2019)
Various research and facts on the field show that students' mathematics learning achievement in Indonesia has not been satisfactory. This is due to various factors, one of which is the method of learning and the ability of students. One of the cognitive abilities that play a role in the success of students in learning mathematics is the ability of mathematical connections. In addition, affective ability is also very important role, one of them ability self efficacy. Between the ability of mathematical connections and self efficacy is positively correlated which became one of the determinants of the success of learning mathematics students. This article intends to examine the effect of applying Contextual Teaching Learning (CTL) model to the ability of mathematical connection and student self efficacy. The method of writing this article is a study of literature sourced from previous studies and related journals.